Students' Opinion on the Faculty Performance Evaluation Instrument - Francis Ann R. Sy; Violeta B. Felisilda (Philippine Association of Institutions for Research, Inc., 2012)
Students' feedback on faculty performance is an influential measure in obtaining the objectives of teaching effectiveness. Southern Leyte State University-Tomas Oppus usually experiences student evaluation reactions on faculty performance. Considering that success of the evaluation process is the instrument itself, this research dealt with students' degree program profile and academic performance; determined their opinion on the criteria's appropriateness and the instrument's validity, reliability, objectivity, and utility and their attitude upon it; and, determined relationship between academic performance and degree program on opinions of the four criteria. Through the descriptive one shot survey, stratified sampling was employed to college freshmen, juniors and seniors with different courses of SY 2010-2011. The mean, percentage, frequency, and chisquare were used. The students' opinion on the appropriateness of the criteria was very appropriate and very high on the four criteria. They manifested positive attitude on the instrument. Their academic performance and degree program have no significant relationship with their opinion on the instrument. Student's opinion of the evaluation instrument was very appropriate, yet, it has to be revisited because some items, though minimal, were moderately appropriate.